DEFINISI DAN KONSEP MANAJEMEN PEMASARAN PENDIDIKAN - Ayu Sofya; Saipul Annur; Baharuddin Baharuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Educational marketing management is an important strategy for educational institutions in building a positive image, enhancing public trust, and strengthening long-term relationships with students and parents. This article aims to examine the concepts, objectives, functions, and marketing mix strategies in educational marketing management through a literature review approach. Data were obtained by analyzing various books and scholarly articles relevant to the topic of educational marketing management. The findings indicate that the objectives of educational marketing management include improving service quality, strengthening institutional reputation, fostering service innovation, increasing operational efficiency, and enhancing public satisfaction and loyalty. The functions of educational marketing management encompass planning, implementation, control, evaluation, human resource management, and institutional branding. Educational marketing mix strategies integrate elements of product, price, promotion, place, service processes, human resources, and physical evidence to create high-quality learning experiences and sustainable institutional competitiveness. The systematic implementation of educational marketing management has been shown to improve service quality, attract new students, and maintain institutional sustainability and public trust. This article is expected to serve as a conceptual reference for the development of effective and adaptive educational marketing strategies in response to changing societal needs. ABSTRAK Manajemen pemasaran pendidikan merupakan strategi penting bagi lembaga pendidikan dalam membangun citra positif, meningkatkan kepercayaan masyarakat, serta memperkuat hubungan jangka panjang dengan peserta didik dan orang tua. Artikel ini bertujuan untuk mengkaji konsep, tujuan, fungsi, dan strategi bauran pemasaran pendidikan berdasarkan pendekatan studi kepustakaan. Data diperoleh melalui analisis berbagai buku dan artikel ilmiah yang relevan dengan topik manajemen pemasaran pendidikan. Hasil kajian menunjukkan bahwa tujuan manajemen pemasaran pendidikan mencakup peningkatan kualitas layanan, penguatan reputasi lembaga, pengembangan inovasi layanan, efisiensi operasional, serta peningkatan kepuasan dan loyalitas masyarakat. Fungsi manajemen pemasaran pendidikan meliputi perencanaan, implementasi, pengendalian, evaluasi, pengelolaan sumber daya manusia, dan penguatan branding lembaga. Strategi bauran pemasaran pendidikan mengintegrasikan unsur produk, harga, promosi, lokasi, proses layanan, sumber daya manusia, dan bukti fisik guna menciptakan pengalaman belajar yang berkualitas dan berdaya saing. Penerapan manajemen pemasaran pendidikan secara sistematis terbukti mampu meningkatkan mutu layanan, menarik peserta didik baru, serta menjaga keberlanjutan dan kepercayaan masyarakat terhadap lembaga pendidikan. Artikel ini diharapkan menjadi referensi konseptual dalam pengembangan strategi pemasaran pendidikan yang efektif dan adaptif terhadap perubahan kebutuhan masyarakat.